2015
DOI: 10.1017/s0007114515002573
|View full text |Cite
|
Sign up to set email alerts
|

Acute consumption of a caffeinated energy drink enhances aspects of performance in sprint swimmers

Abstract: This study investigated the effect of a caffeinated energy drink on various aspects of performance in sprint swimmers. In a randomised and counterbalanced order, fourteen male sprint swimmers performed two acute experimental trials after the ingestion of a caffeinated energy drink (3 mg/kg) or after the ingestion of the same energy drink without caffeine (0 mg/kg; placebo). After 60 min of ingestion of the beverages, the swimmers performed a countermovement jump, a maximal handgrip test, a 50 m simulated compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 30 publications
3
55
1
6
Order By: Relevance
“…The scientific evidence regarding the performance-enhancing properties of caffeine has been found in short-term high-intensity sports modalities [2], team sports competitions [3,4,5], and endurance-based exercise [6,7]. Moreover, the pre-exercise ingestion of caffeine is effective in increasing physical performance in resistance activities [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scientific evidence regarding the performance-enhancing properties of caffeine has been found in short-term high-intensity sports modalities [2], team sports competitions [3,4,5], and endurance-based exercise [6,7]. Moreover, the pre-exercise ingestion of caffeine is effective in increasing physical performance in resistance activities [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While most investigations have reported the benefits of caffeine on exercise activities in a group of individuals, some investigations have reported that not all individuals experience enhanced exercise performance after the ingestion of moderate doses of caffeine [2,21,22,23]. In fact, these investigations have identified individuals with minimal ergogenic effects, or even slightly declined exercise performance, after the intake of caffeine [2,21,22,23], suggesting the existence of different physiological responses to the intake of the same dose of caffeine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects: To analyze side-effects resulting from caffeine ingestion in the following night hours a non-parametric test for dichotomic variables was recorded, this questionnaire has been previously used to analyze side-effects from caffeine in sport 2,15,21,22 . The next morning of each training sleep quality, nervousness, gastrointestinal problems and other discomforts related to caffeine ingestion were evaluated in soccer players with a questionnaire including 8 items on a yes/no scale.…”
Section: Initial Tiredness Scalementioning
confidence: 99%
“…In a sport and exercise context, caffeine has been consistently shown to aid a variety of endurance based tasks [5][6][7] with significant enhancements in cycling [8,9], swimming [10] and rowing [11] performance all being reported. On the other hand, both supporting [12][13][14][15][16][17][18] and contradicting [19][20][21][22][23] research has been published in terms of muscular endurance.…”
mentioning
confidence: 99%